BISON: A Flexible Code for Advanced Simulation of the Performance of Multiple Nuclear Fuel Forms. (3rd July 2021) - Williamson, Richard L.; Hales, Jason D.; Novascone, Stephen R.; Pastore, Giovanni; Gamble, Kyle A.; Spencer, Benjamin W.; Jiang, Wen; Pitts, Stephanie A.; Casagranda, Albert; Schwen, Daniel; Zabriskie, Adam X.; Toptan, Aysenur; et al.
Abstract: BISON is a nuclear fuel performance application built using the Multiphysics Object-Oriented Simulation Environment (MOOSE) finite element library. One of its major goals is to have a great amount of flexibility in how it is used, including in the types of fuel it can analyze, the geometry of the fuel being modeled, the modeling approach employed, and the dimensionality and size of the models. Fuel forms that can be modeled include standard light water reactor fuel, emerging light water reactor fuels, tri-structural isotropic fuel particles, and metallic fuels. BISON is a platform for research in nuclear fuel performance modeling while simultaneously serving as a tool for the analysis of nuclear fuel designs. Recent research in BISON includes techniques such as the extended finite element method for fuel cracking, exploration of high-burnup light water reactor fuel behavior, swelling behavior of metallic fuels, and central void formation in mixed-oxide fuel. BISON includes integrated documentation for each of its capabilities, follows rigorous software quality assurance procedures, and has a growing set of rigorous verification and validation tests.